Interleukins 4 and 13 in Asthma: Key Pathophysiologic Cytokines and Druggable Molecular Targets - Pelaia, Corrado; Heffler, Enrico; Crimi, Claudia; Maglio, Angelantonio; Vatrella, Alessandro; Pelaia, Girolamo; Canonica, Giorgio Walter (Frontiers in Pharmacology, 2022)
Interleukins (IL)-4 and -13 play a pivotal role in the pathobiology of type-2 asthma. Indeed, IL-4 is crucially involved in Th2 cell differentiation, immunoglobulin (Ig) class switching and eosinophil trafficking. IL-13 cooperates with IL-4 in promoting IgE synthesis, and also induces nitric oxide (NO) production, goblet cell metaplasia and fibroblast proliferation, as well as elicits contractile responses and hyperplasia of airway smooth muscle cells. IL-4 and IL-13 share common signaling pathways, activated by the binding of both cytokines to receptor complexes including the α-subunit of the IL-4 receptor (IL-4Rα). Therefore, the subsequent receptor dimerization is responsible for the pathophysiologic effects of IL-4 and IL-13. By selectively blocking IL-4Rα, the fully human IgG4 monoclonal antibody dupilumab behaves as a dual receptor antagonist of both IL-4 and IL-13. Through this mechanism of action, dupilumab exerts effective therapeutic actions in type-2 inflammation, thus decreasing asthma exacerbations, FeNO (fractional exhaled NO) levels, and the intake of oral corticosteroids (OCS). In addition to being approved for the add-on biological therapy of severe asthma, dupilumab has also been licensed for the treatment of nasal polyposis and atopic dermatitis.